DAMPAK DIMENSI EKUITAS MEREK DALAM MEMBENTUK MINAT BELI ULANG - Vera Verdilla; Albari Albari (Universitas Kristen Maranatha, 2018)
Along with the times, the economy grew by leaps and bounds. Many brands are popping up in the market. Brands competing to attract the attention of consumers. To cope with competition management must first understand the importance of the power contained within the dimensions of their brand equity. For that empirical research is intended to explain the relationship between the dimensions of brand equity, especially the positive influence of consumer repurchase intention. The population in this study are those who have never made a purchase in the clothing brand